The Utilization of E-Waste in Asphalt Pavement: A Review - Bayagoob, Ali A. S.; Péter, Füleki (Journal of Advanced Industrial Technology and Application, 2022)
E-waste generation has increased due to the rapid rate of modernization and technology development. The total amount of E-waste is estimated to be 65.3 million metric tonnes by 2025 globally. This rapid growth is making E-waste management a global issue. Electronic waste includes electronic devices, which reached their end-of-life such as computers, screens, televisions, smartphones, tablets, radios, air conditioners and refrigerators. The disposal of electronic waste is difficult because of highly toxic and non-degradable plastic contents and metals such as lead, lithium, copper and chromium, which can result in adverse effects on the environment. To deal with this issue, several studies have confirmed that electronic waste can be used in experimental works related to asphalt pavements, bitumen and bituminous mixes can be modified in order to improve the performance of bituminous concrete mixtures. According to the obtained results from previous and ongoing research efforts, the use of E-waste plastics in asphalt pavement materials have enhanced the asphalt pavement properties such as resistance to permanent deformation, high-temperature properties and asphalt stability. This paper affords an overview of the studies that have been conducted using E-waste in flexible pavement. This review transacts through the applications of electronic-waste plastics within the asphalt modification in an environmentally friendly manner. Furthermore, the impact of E-waste on the durability, stability, viscosity, penetration, softening point and low and high-temperature performance are discussed.